Brazilian Validation of Centrality of Religiosity Scale (CRS-10BR and CRS-5BR) - Esperandio, Mary Rute Gomes (Religions, 2019)
The centrality of religiosity scale (CRS), available in three versions (with 5, 10 and 15 items), is a measuring instrument that identifies the central importance of religiosity in the psychological construction and in the behavior of an individual. According to the literature, five components together express the centrality of religion in life: Public practice, private practice, ideological, intellectual, and religious experience. These components are the ground on which religious constructs are formed and activated. For the validation of the scale in the Brazilian cultural context, two versions were tested (CRS-10BR and CRS-5BR) with data collected from a general population (N = 687). Exploratory Factor Analysis (N = 334) resulted in a five-factor solution congruent to CRS-10BR. Confirmatory Factor Analysis (N = 353) demonstrated that a five-factor solution (Intellect, Ideology, Private Practice, Public Practice and Religious Experience) indicated better fit indexes than the single-factor solution of five items (CRS-5BR). Thus, CRS-10BR is recommended to capture CRS full construct. However, the CRS-5BR version can be considered suitable for use in the Brazilian population when the context is demanding simpler and faster data collection.